Studying inner ear protein–protein interactions using FRET and FLIM - Hallworth, Richard (2006)
Molecular genetic studies of the inner ear have recently revealed a large number of previously undescribed proteins, but their functions remain unclear. Optical methods such as FRET and FLIM are just beginning to be applied to the study of functional interactions between novel inner ear proteins. This review discusses the various methods for employing FRET and FLIM in protein–protein interaction studies, their advantages and pitfalls, with examples drawn from inner ear studies.